Development and validation of an environmental heat strain risk assessment (EHSRA) index using structural equation modeling based on empirical relations - Saeid Yazdanirad; Farideh Golbabaei; Abbas Rahimi Foroushani; Mohammad Reza Monazzam; Habibollah Dehghan (Komiyama Printing Co. Ltd, 2020)
Abstract Background Need to a simple, available, accurate, comprehensive, and valid indicator is felt to assess thermal effects. Therefore, the present study was aimed to develop and validate the environmental heat strain risk assessment (EHSRA) index using structural equation modeling (SEM) based on empirical relations. Methods This cross-sectional study was performed on 201 male workers in environments with various climatic conditions. The heart rate and tympanic temperature of the individuals were monitored at times of 30, 60, and 90 min after beginning the work. At these times, values of dry temperature, wet temperature, globe temperature, and air velocity were also measured and metabolism rate and clothing thermal insulation value were estimated. At the end, a theoretical model was depicted in AMOS software and obtained coefficients were applied to develop a novel index. The scores of this indicator were categorized into four risk levels via ROC curves and validate using linear regression analysis. Results Indirect effect coefficients of the globe temperature, dry temperature, wet temperature, air velocity, metabolism, and clothing thermal insulation variables on the tympanic temperature were computed by 0.77, 0.75, 0.69, 0.24, 0.49, and 0.39, respectively. These coefficients were applied to develop the index. Optimal cut-off points of boundaries between risk levels included 12.02, 15.88, and 17.56. The results showed that the EHSRA index justified 75% of the variations of the tympanic temperature (R 2 = 0.75). Conclusions The novel index possesses appropriate validity. It was suggested that this indicator is applied and validated in various environments in the next studies.